Encapsulated papillary carcinoma of the breast: a case report - Errami, Lamyae; Graiti, Ghizlane; Lamzouri, Oussama; Bellajdel, Btissam; Chatbi, Zainab; Slama, Loubna; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Encapsulated papillary carcinoma (EPC) of the breast is a rare form of ductal carcinoma characterized by its development within a cystic space surrounded by a fibrous capsule. Due to its uncommon nature, the in situ or invasive status of EPC can be challenging to establish, particularly through biopsy. Surgical intervention is the primary treatment, and the need for adjuvant therapy remains a subject of debate. This case report describes the diagnosis, management, and outcome of EPC in a premenopausal woman. A 39-year-old premenopausal woman presented with a 12-month history of a painless, palpable mass in the right breast. There was no history of nipple discharge, smoking, oral contraceptive use, or familial breast or ovarian cancer. Clinical examination revealed a 4×7 cm, well-circumscribed, soft, oval, and mobile mass in the superior outer quadrant of the right breast, with no evidence of axillary, cervical, or supraclavicular lymphadenopathy. Mammography identified two adjacent retroareolar masses (47×36 mm and 43×28 mm), and ultrasonography showed one predominantly cystic lesion with a solid component and a second anechoic lesion, both classified as ACR 4, indicating suspicious malignancy. A lumpectomy was performed, and histopathological analysis confirmed encapsulated papillary carcinoma. Immunohistochemistry showed tumor cells positive for p63, p40, CK5/6, AML, and estrogen receptor (ER) with a Ki-67 proliferation index of less than 5%, suggesting a low proliferative rate. Complete surgical excision was achieved with no further adjuvant therapy deemed necessary due to the low proliferation index. At the 6-month follow-up, the patient remained asymptomatic with no evidence of recurrence. This case highlights the importance of considering EPC in the differential diagnosis of breast masses in premenopausal women. Early recognition and appropriate surgical management are crucial for favorable outcomes. Further research is needed to determine optimal management strategies for EPC, particularly in younger patients.